Temperature effect in physicochemical and bioactive behavior of biogenic hydroxyapatite obtained from porcine bones - Forero-Sossa, P. A. (Sci Rep, 2021)
Biogenic hydroxyapatite (BHAp) is a widely used material in the biomedical area due to its similarities with the bone tissue mineral phase. Several works have been spotlighted on the thermal behavior of bone. However, little research has focused on determining the influence of calcination temperature in the physicochemical and bioactive properties of BHAp. In this work, a study of the physicochemical properties’ changes and bioactive response of BHAp produced from porcine femur bones using calcination temperatures between 900 to 1200 °C was conducted. The samples’ structural, morphological, and compositional changes were determined using XRD, SEM, and FTIR techniques. XRD results identified three temperature ranges, in which there are structural changes in BHAp samples and the presence of additional phases. Moreover, FTIR results corroborated that B-type substitution is promoted by increasing the heat treatment temperature. Likewise, samples were immersed in a simulated biological fluid (SBF), following the methodology described by Kokubo and using ISO 23317:2014 standard, for 3 and 7 days. FTIR and SEM results determined that the highest reaction velocity was reached for samples above 1000 °C, due to intensity increasing of phosphate and carbonate bands and bone-like apatite morphologies, compared to other temperatures evaluated.